"Brand play" versus "Brand attack": the subversion of brand meaning in non-collaborative co-creation by professional artists and consumer activists. Issue 3 (14th May 2018) - Kristal, Samuel; Baumgarth, Carsten; Henseler, Jörg
Abstract : Purpose: This paper aims to investigate the ways in which "non-collaborative co-creation" can affect brand equity as perceived by independent observers. It reports a study of the different effects on that perception attributable to non-collaborative co-creation that takes the form of either "brand play" or "brand attack" and is executed either by established artists or mainstream consumers. Design/methodology/approach: A 2 × 2 between-subjects experiment (brand play versus brand attack; consumer versus artist) measured observers' perception of brand equity before and after exposure to purpose-designed co-created treatments. Findings: Non-collaborative co-creation has a negative effect on observers' perceptions of brand equity and brand attack, causing a stronger dilution of brand equity than brand play. Artists either mitigate the dilution or have a positive effect on those perceptions. Research limitations/implications: Future research could usefully investigate the relative susceptibility of brands to non-collaborative co-creation, the effects on brands of higher complexity than those in our experiment, exposed in higher-involvement media, and the effects of more diverse forms of co-creation. Practical implications: Brand managers must recognise that co-creation carries considerable risks for brand equity. They should closely monitor and track the first signs of non-collaborative co-creation in progress. It could be beneficial to recruit artists as co-creators of controlled brand play. Originality/value: This study offers a more complete insight into the effect of non-collaborative co-creation on observers' perceptions of brand equity than so far offered by the existing literature. It connects the fields of brand management and the arts by investigating the role and impact of artists as collaborative or non-collaborative co-creators of brand equity.